Heavy metal levels in patients with ineffective erythropoiesis. Issue 4 (August 2017) - Bayhan, Turan; Ünal, Şule; Çırak, Eyüp; Erdem, Onur; Akay, Cemal; Gürsel, Orhan; Eker, İbrahim and Karabulut, Erdem and Gümrük, Fatma
Abstract: Objectives: Iron is taken into enterocytes at the duodenum via apical divalent metal-ion transporter 1 protein. Besides iron, divalent metal-ion transporter 1 also transports other divalent metals. We aimed to investigate blood heavy metal levels in patients with ineffective erythropoiesis. Methods: Blood levels of heavy metals including Pb, Al, Cd, Cr, Co, Cu, and Zn were measured in patients with thalassemia major (TM), thalassemia intermedia (TI), congenital dyserythropoietic anemia (CDA), and age- and sex-matched healthy controls. Results: Blood samples were obtained from 68 patients (51 patients with TM, 8 with TI, 9 with CDA), and a control group that included 65 volunteers. Patients with TM were found to have lower Al, Pb, and Zn, and higher Cd levels compared with the control group. The patients treated with deferasirox were further analyzed and Pb and Zn levels were found lower compared with the control group. Discussion: Patients with TM had tendency to have elevated levels of plasma cadmium; however, the median level was not at a toxic level. Increased metal-ion transporter 1 activity may cause heavy metal accumulation, but deferasirox chelation may be protective against heavy metals besides iron.